Warranty Management and Product Manufacture - Murthy, D. N. Prabhakar; Blischke, Wallace R. (Springer Series in Reliability Engineering, 2006)
Purchasers of manufactured goods demand assurance that the purchased product will perform satisfactorily over its expected life. Warranties play a vitally important role in providing this assurance, in two ways. Firstly, warranty terms can provide a promise of protection in the event of a product failure. Secondly, effective warranty service can assure customer satisfaction in the event of a warranty claim. Successful use of both of these requires proper warranty management. The authors of Warranty Management and Product Manufacture have developed "Stage-3" warranty management, that views warranties from a strategic perspective, beginning with a warranty strategy that is linked to technical and commercial planning from the very start of the product development process. The aim of warranty management is to achieve the overall business objectives by focussing on both product performance assurance as well as ensuring customer satisfaction, the ultimate goal of warranty management. Warranty Management and Product Manufacture provides guidelines for achieving this goal. Written by two of the world's leading experts in warranty management, this monograph details the most up-to-date thinking in this key area of product manufacture. It will be an invaluable guide for managers in product development, production and marketing as well as graduate students in business and operations management and industrial engineering. The Springer Series in Reliability Engineering publishes high-quality books in important areas of current theoretical research and development in reliability, and in areas that bridge the gap between theory and application in areas of interest to practitioners in industry, laboratories, business, and government.